PENENTUAN HARGA POKOK PRODUKSI BALOK KAYU TERHADAP BESARNYA LABA PERUSAHAAN DENGAN METODE FULL COSTING (STUDI KASUS PT. SUWARNI AGRO MANDIRI SINGOSARI MALANG) - Susan Agung Priyanto; Hasan Basori (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2019)
This research aims for pricing order of the amount corporate earning by Full Costing Methods at PT. SUWARNI AGRO MANDIRI of Singosari District and Malang Regency. This type of research is Description Research that is Case Study. The main focus of this research is limited to the issue of the determination of the cost of production of the large profits earned by the industry or the company. Data collecting methods are observation, interview, and documentation. This research is doing at PT. Suwarni Agro Mandiri of Singosari District and Malang Regency.by using with Full Costing Methods.